2017
DOI: 10.1093/nar/gkx187
|View full text |Cite
|
Sign up to set email alerts
|

CDK12 regulates alternative last exon mRNA splicing and promotes breast cancer cell invasion

Abstract: CDK12 (cyclin-dependent kinase 12) is a regulatory kinase with evolutionarily conserved roles in modulating transcription elongation. Recent tumor genome studies of breast and ovarian cancers highlighted recurrent CDK12 mutations, which have been shown to disrupt DNA repair in cell-based assays. In breast cancers, CDK12 is also frequently co-amplified with the HER2 (ERBB2) oncogene. The mechanisms underlying functions of CDK12 in general and in cancer remain poorly defined. Based on global analysis of mRNA tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(131 citation statements)
references
References 86 publications
4
123
3
1
Order By: Relevance
“…SNRNP70, a component of the U1 snRNP complex was identified as a potential phosphorylation substrate of CDK12/13 in our study; hence, it is quite possible that its decreased phosphorylation could partly account for the increased usage of alternate polyadenylation sites in DDR and other long genes. This could also explain why in contrast to findings in other studies implicating CDK12 in splicing regulation 32,43 , CDK12 inhibition did not lead to major splicing alterations, most likely because transcription was terminated well before it reached the 3′ splice sites 53 .…”
Section: Inhibition Of Cdk12 By Thz531 Results In Increased Transcripcontrasting
confidence: 58%
See 2 more Smart Citations
“…SNRNP70, a component of the U1 snRNP complex was identified as a potential phosphorylation substrate of CDK12/13 in our study; hence, it is quite possible that its decreased phosphorylation could partly account for the increased usage of alternate polyadenylation sites in DDR and other long genes. This could also explain why in contrast to findings in other studies implicating CDK12 in splicing regulation 32,43 , CDK12 inhibition did not lead to major splicing alterations, most likely because transcription was terminated well before it reached the 3′ splice sites 53 .…”
Section: Inhibition Of Cdk12 By Thz531 Results In Increased Transcripcontrasting
confidence: 58%
“…Because previous studies point to a role for CDK12 in splicing regulation 10,32,43,44 , we determined whether aberrant splicing could explain the elongation defect seen with THZ531 treatment. Analysis of the nascent transcriptomic data showed that in general, there was a paucity of significantly altered splicing events following THZ531 treatment.…”
Section: Cdk12/13 Inhibition Induces Minimal Splicing Alterations In mentioning
confidence: 99%
See 1 more Smart Citation
“…As the results show ( Figure 5D), the differentially expressed proteins were mainly involved mRNA splicing, which is usually enhanced when cancer cells go through migration or invasion. [10][11][12] In dense environments, proteins associated with cytoskeleton re-organization also increased in 4T1 cells. The cytoskeleton has roles in organelle transport, cell division, signalling, and motility, and it is closely related to cancer metastasis.…”
Section: Bioinformatic Information For Differentially Expressed Promentioning
confidence: 96%
“…Among the top 5% (51/1012) of our ranked genes is CDK12 (rank 40), which is impacted by multiple but non-overlapping types of alterations. Alterations within its protein kinase domain have been shown to cause dysregulation of DNA repair in cancer [114][115][116][117] . Aggregating over all alterations, we find 87 samples that have an alteration in this domain, with 64 (74%) patients having no DNA, but only a RNA alteration in the domain.…”
Section: Known and Novel Candidate Driver Genes Are Recurrently Altermentioning
confidence: 99%